“Taboos, prohibitions and secrets in Hugo Hamilton’s The Speckled People” - Cotta Ramusino, Elena (Linguæ & - Journal of Modern Languages and Cultures, 2024)
The Speckled People, the 2003 memoir by Hugo Hamilton, narrates the growth of little Hanno from childhood in the 1950s in Ireland to early manhood. The family life pivots on the major taboo dominating their home: the absolute prohibition on the use of English, implemented through harsh punishments. This taboo is functional to the reversal of Irish history planned by his nationalist father. This article aims to analyse the consequences of this taboo for the protagonist. This ban on the use of English has devastating psychological consequences for Hanno: a perennial sense of displacement, constant queries about himself and where he belongs and the impossibility of making friends. The father’s original taboo, detrimental to his own identity, is his planned oblivion of his own father, because he served in the British Navy during WWW I and spoke English – a taboo issue in Irish society until at least the 1980s.